Chemical principles underpinning the performance of the metal–organic framework HKUST-1. Issue 7 (15th July 2015) - Hendon, Christopher H.; Walsh, Aron
<x xml:space="preserve">Abstract</x> HKUST-1 has emerged as the bastion of multifunctional hybrid solids; we discuss the past, present and future of Cu-based metal–organic frameworks.